Pengembangan Produk Pindang Desa Kusamba Melalui Aplikasi Teknologi Tepat Guna dan Pengemasan Vakum - Pande Ayu Naya Kasih Permatananda (Scopus ID: 57203963009); I Gde Suranaya Pandit; I Ketut Irianto (Universitas Warmadewa, 2020)
Fish shelters in Kusamba are traditional fish shelters and still to use very conventional tools, the workers are also not trained and an educated personnal in food production, so that the boiled fish produced by Kusamba village does not have good quality, packaging tends to be haphazard and its safety is questionable. To improve the quality of processed fish products in Kusamba Village, the community service aims to conduct training and simulations that can help Kusamba Village workers and elevate the Kusamba boiled fish to become an international-class product. The service methods employed include counseling on the importance of food processing hygiene, hand washing exercises, demonstration of screening, vacuum packaging training, and marketing simulations through social media. Evaluation and monitoring will be carried out through observation during the activities and the pretest and posttest questionnaires. The results of these community service activities have succeeded in increasing the knowledge and skills of workers in applying appropriate technology applications from processing to packaging of boiled fish.